CEHTM certified ethical hacker : exam guide - Walker, Matt (McGraw-Hill New YorkUS, 2012)
Presents the specialised set of tools, techniques, knowledge and skills to bypass computer security measures to enable becoming a successful ethical hacker as well as to pass the EC-Council's version 7 of the Certified Ethical Hacker examination.